2019
DOI: 10.1186/s12873-019-0222-9
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of alcohol and illicit drug use among injured patients presenting to the emergency department of a national hospital in Tanzania: a prospective cohort study

Abstract: BackgroundAlcohol and illicit drugs have been found to be major contributing factors leading to severe injuries in a variety of settings. In Tanzania, the use of these substances among injured patients has not been studied. We investigated the prevalence of positive tests for alcohol and illicit drug use among injured patients presenting to the emergency medicine department (ED) of Muhimbili National Hospital (MNH).MethodsThis was a prospective cohort study of a consecutive sample of patients > 18 years of age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…The association of alcohol and others drugs use and accidents was observed in brazilian and worldwide studies (Mundenga et al, 2019;Andrecceutti et al, 2018;Bakke, Normann, Ekeberg & Bachs, 2016;Lasebikan & Adebayo, 2013;Legrand, Silverans, Paepe, Buylaert & Verstraete, 2013), which corroborate to those found in this study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The association of alcohol and others drugs use and accidents was observed in brazilian and worldwide studies (Mundenga et al, 2019;Andrecceutti et al, 2018;Bakke, Normann, Ekeberg & Bachs, 2016;Lasebikan & Adebayo, 2013;Legrand, Silverans, Paepe, Buylaert & Verstraete, 2013), which corroborate to those found in this study.…”
Section: Discussionsupporting
confidence: 90%
“…While many studies worldwide use the patient's verbal report or a screening tool to detect the use of alcohol and illicit drugs in patients with physical trauma, our study and other studies have shown that the analytical toxicological test is more accurate and provides the evidence for psychoactive substances abuse, allowing information when patients are unable to do so and avoiding an incorrect estimate of drug and alcohol use. However, one of the main limitations of using toxicological tests is their high cost, a reality in most low-and middle-income countries (Mundenga et al, 2019;UNODC, 2019;WHO, 2018b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We calculated our sample size to determine the number of patients needed to report a proportion of positive screens with a 5% margin of error. Based on data from Mundenga et al, we assumed a positive screening rate of roughly 50% in our study population [8] . We calculated that assessment of 385 subjects would provide a confidence level of 95% that our point estimate of the positive screening rate would fall within ±5% of the actual value.…”
Section: Methodsmentioning
confidence: 99%
“…In Tanzania, intoxication among drivers has been poorly studied but appears to be common, with some noting, “it is an open secret that drivers drink and drive with impunity.” [7] Preliminary work by Mundenga et al (2019) assessed for objective evidence of drug and alcohol use in trauma patients presenting to the EC of Muhimbili National Hospital (MNH) within 12 h of injury. They found that 49% of patients tested positive for alcohol and 36% of patients tested positive for illicit drugs [8] . While this study included all trauma patients, data on drug and alcohol use in drivers can help inform targeted interventions.…”
Section: Introductionmentioning
confidence: 99%